1994
DOI: 10.1093/oxfordjournals.aje.a117190
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study of Silicon Carbide Production Workers

Abstract: Silicon carbide is produced by a chemical reaction at high temperature between free crystalline silica and petroleum coke. The process generates airborne fibers and fibrogenic dusts such as alpha-quartz and cristobalite, which are also potentially carcinogenic. The authors report that this is the first cohort study in this industry. The study was carried out among 585 Québec silicon carbide production workers who had worked at any time from 1950 to 1980. Follow-up was to December 31, 1989, and 167 deaths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
20
2
Order By: Relevance
“…Both addressed lung cancer in relation to cumulative exposure to total dust and indicated an exposureresponse relationship between lung cancer incidence and cumulative dust exposure. However, the Canadian study (11) was very small (N=585), and -even if the SMR of lung cancer showed increasing risk estimates with increasing exposure -the power of the study was too weak to give statistically significant results (11). In the Norwegian study (12), the non-exposed group had a risk of 0.6 of the expected number, whereas the SIR increased to 1.9 in the group at the lowest level of exposure, flattened out, and showed only a limited increase with increasing exposure levels.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Both addressed lung cancer in relation to cumulative exposure to total dust and indicated an exposureresponse relationship between lung cancer incidence and cumulative dust exposure. However, the Canadian study (11) was very small (N=585), and -even if the SMR of lung cancer showed increasing risk estimates with increasing exposure -the power of the study was too weak to give statistically significant results (11). In the Norwegian study (12), the non-exposed group had a risk of 0.6 of the expected number, whereas the SIR increased to 1.9 in the group at the lowest level of exposure, flattened out, and showed only a limited increase with increasing exposure levels.…”
mentioning
confidence: 96%
“…In 1919, Winslow et al (10) reported an increased risk of tuberculosis among SiC workers and commented: "We have every reason to expect … that dusts of this nature should be exceedingly deleterious to health." The first published study on cancer risk among SiC workers (11) showed an increased mortality from cancer of the lung [standardized mortality ratio (SMR) 1.69, 95% confidence intervals (95% CI) 1.09-2.52] and stomach cancer (SMR 2.18, 95% CI 0.88-4.51). More recently, the Norwegian Cancer Registry performed a cancer incidence study among 2620 SiC workers in three Norwegian plants (12).…”
mentioning
confidence: 99%
“…As occupational and environmental inhalation exposure to asbestos causes pulmonary fibrosis 1) , a number of manmade mineral fibers (MMMFs) have been developed as a substitute, but, because of their similar physiochemical properties, MMMFs are thought to have adverse biological effects similar to those of asbestos 2) . Animal studies have shown that silicon carbide whisker (SiCW), which is used in abrasive and refractory materials, and the production of parts for electronic equipment, cause fibrosis 3,4) , suggesting that SiCW might have a fibrogenic potential.Surfactant protein 5) produced by mainly type II alveolar epithelial cells acts as a control tower responsible for guiding the secretion and re-uptake of phospholipid which decreases alveolar surface tension, and through the prevention of alveolar collapse, these are thought to play contributory roles in preventing the progress of fibrotic processes 6,7) . Decreases in the levels of SP-A and SP-C mRNA have been reported to occur in the bronchoalveolar lavage fluid (BALF) of patients with idiopathic pulmonary fibrosis 5,8) , and SP-A is thought to be a good biomarker of lung injury and pulmonary fibrotic activity.…”
mentioning
confidence: 99%
“…As occupational and environmental inhalation exposure to asbestos causes pulmonary fibrosis 1) , a number of manmade mineral fibers (MMMFs) have been developed as a substitute, but, because of their similar physiochemical properties, MMMFs are thought to have adverse biological effects similar to those of asbestos 2) . Animal studies have shown that silicon carbide whisker (SiCW), which is used in abrasive and refractory materials, and the production of parts for electronic equipment, cause fibrosis 3,4) , suggesting that SiCW might have a fibrogenic potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation